PERFORMANCE ANALYSIS OF ROE, ROA, BOPO, FDR AFTER CONVERSION TO NOM BANK NTB SYARIAH - Lalu Mifta Respati Rizki; Yaser Taufik Shamlan (UIN Mataram, 2022)
This study aims to analyze the effect of the performance relationship, analyze thecontribution, and find out how long the shock period of each variable is; (1) BOPO, (2) FDR, (3)ROA, and (4) ROE against Net Operating Margin at Bank NTB Syariah. This study uses theTheory of Good Corporate Governance approach, then the data is processed using the VARVECM and ECM methods on the EViews 12 application. There are two analysis results in thisstudy, the first through the VAR-VECM analysis and the second through the ECM, the results ofthe VAR-VECM test in the equation model have not found a balance both in the long and shortterm, but on the other hand there are shocks experienced by the independent variables. NOMthrough the dependent variables BOPO, FDR, ROA, and ROE worth 60.93%, 9.83%, 7.54%, and4.74%. While the response level of the BOPO variable was positively responsive by 0.012992 bythe NOM variable and was stable in period 25, for other variables such as FDR, ROA, and ROEthe response fluctuated and did not experience value stability. In contrast to the results of theECM test where in this test the variables that have a long-term effect are the BOPO, ROA, andROE variables with the probability values of 0.000, 0.0081, and 0.0375 while for the short-termperiod the variables that have an effect are only the BOPO variable with a probability value that isworth 0.0341